Implementasi Pembelajaran Kontekstual Terhadap Peningkatan Ranah Afektif Siswa - Eneng Nurjanah; Suci Susanti; Suharyanto H. Soro; Ida Tejawiani (Global Education Journal, 2026)
This research is motivated by the importance of developing students' affective domain as a primary aspect in education, including attitudes, values, responsibility, and discipline. The reality in the field shows that classroom learning emphasizes cognitive aspects more so that the development of the affective domain is not optimal. This study aims to describe the implementation of contextual learning in improving students' affective domain. The researcher used a case study approach with 24 students attending the Pancasila Education subject. Data collection methods were through participatory observation, in-depth interviews, and documentation. Data analysis techniques included data collection, data reduction, data presentation, and conclusion drawing. Data validity was checked through triangulation of sources and techniques. The results of the study showed that the application of contextual learning involving daily experiences, the surrounding environment, and real activities was able to foster and improve positive attitudes, a sense of responsibility, cooperation, and discipline in students with a total implementation score reaching 26 out of a maximum score of 28 (Very Good Category). Contextual learning has proven effective in developing the affective domain of elementary school students.